Dimensioning of nursing team at neonatal intensive care unit: real versus ideal / Dimensionamento de enfermagem em unidade de terapia intensiva neonatal: real versus ideal - Aline Patrícia Vicente Franco; Beatriz Pera de Almeida Hamasaki; Luciana Renata de Puiz; Gisele Hespanhol Dorigan; Ariane Polidoro Dini; Elenice Valentim Carmona (Revista de Pesquisa Cuidado é Fundamental Online)
Objective: to compare the workload at a neonatal unit, according to Nursing Activities Score, and the dimensioning of nursing staff. Methods: cross-sectional study at a teaching unit with 30 beds. Data collection took place from October 6 to December 6, 2017, and data were analyzed according to descriptive statistics. Results: the sample of 115 neonates, totaling 1944 measurements. The average workload score was 73%. The unit has 107 nursing professionals, while should has 137. The proportion of registered nurses was lower than recommended (34%), whereas the proportion of nursing technicians was higher than recommended (66%). Conclusion: there was an imbalance between workload and number of professionals in nursing staff. Tools as Nursing Activities Score should be applied for supporting the staff dimensioning, since workload can impact the health outcomes and patient safety.